2008
DOI: 10.20452/pamw.408
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes control and pregnancy outcomes in women with type 1 diabetes treated during pregnancy with continuous subcutaneous insulin infusion or multiple daily insulin injections

Abstract: Objectives. The aim of the study was to compare diabetes control and obstetrical outcomes in pregnant women with type 1 diabetes treated during pregnancy with either continuous subcutaneous insulin infusion (CSII) or multiple daily insulin injections (MDII). Patients and methods. It was a descriptive, retrospective, observational study of 116 Caucasian pregnant women with type 1 diabetes mellitus. Thirty women were treated during pregnancy with continuous subcutaneous insulin infusion (CSII group) and 86 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 18 publications
1
39
0
1
Order By: Relevance
“…[51][52][53]56 The investigators did not find any studies in pregnant women with T1DM that evaluated maternal mortality, microvascular or macrovascular disease, quality of life, any of the process measures, or birth trauma, and no studies were identified that compared the effectiveness of CSII and MDI in pregnant women with pre-existing T2DM.…”
Section: Methods For Insulin Delivery and Glucose Monitoring In Diabementioning
confidence: 99%
See 4 more Smart Citations
“…[51][52][53]56 The investigators did not find any studies in pregnant women with T1DM that evaluated maternal mortality, microvascular or macrovascular disease, quality of life, any of the process measures, or birth trauma, and no studies were identified that compared the effectiveness of CSII and MDI in pregnant women with pre-existing T2DM.…”
Section: Methods For Insulin Delivery and Glucose Monitoring In Diabementioning
confidence: 99%
“…Also, meta-analyses of retrospective studies showed nonsignificant relative risks for rates of C-section (RR = 1.01; 95% CI, 0.86-1.20), [53][54][55][56] severe hypoglycemia (RR = 0.78; 95% CI, 0.23-2.65), [54][55][56] admission to the neonatal intensive care unit (RR = 0.84; 95% CI, 0.43-1.68), 54,55 pre-term delivery (RR = 0.98; 95% CI, 0.67-1.43), [53][54][55][56] and frequency of neonatal hypoglycemia (RR = 1.01; 95% CI, 0.86-1.20). [53][54][55][56] Additionally, metaanalyses for major congenital anomalies showed a pooled RR of 2.12 that favored MDI but was not statistically significant. 55,56 Due to the lack of RCTs, which leads to a high risk of bias of all the above outcomes, the EPC investigators suggested that results were inconclusive.…”
Section: Adults With T1dmmentioning
confidence: 99%
See 3 more Smart Citations